The Quest for the Golden Trout : Environmental Loss and America's Iconic Fish - Thompson, Douglas M. (Douglas Marshall) (Book collections on Project MUSE., 2013)
A river advocate and environmentalist questions some of the unsound methods of conservation and restoration imposed on North American rivers and streams.